The Value of saving : the story of Benjamin Franklin - Johnson, Spencer (La Jolla, CA : Value Comm., Inc. Pub, 1978)
A biref biography of the outstanding eighteenth-century printer, inventor, and statesman, emphasizing the value of saving in his life.
Keywords: Franklin Benjamin, 1706-1970; Statesmen -- United Stated -- Biography; Saving and investment